2016
DOI: 10.15835/nbha44110169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nitrogen Sources and Plant Growth-Promoting Rhizobacteria Inoculation on Growth, Crude Fiber and Nutrient Uptake in Squash (<i>Cucurbita moschata</i> Duchesne ex Poir.) Plants

Abstract: Plant growth promoting rhizobacteria (PGPR, B) have immense potential application in sustainable agriculture as ecofriendly biofertilizers and biopesticides. In this study, the effects of three nitrogen (N) sources (NO 3 -, NH 4 + and NO 3 NH 4 ) and PGPR on growth, crude fiber and nutrient uptake were investigated in squash plants. Some growth parameters [root dry weight (RDW), shoot dry weight (SDW), total plant dry weight (PDW), number of leaves (NL), shoot length (SL), stem diameter (SD) and number of rami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
2
1
1
Order By: Relevance
“…Regarding N concentration, several studies have found that PGPR can increase the N levels in tomato and zucchini shoots [10,63,64]. However, in the present study, PGPR application did not increase the N levels in plant shoots in both experiments.…”
Section: Discussioncontrasting
confidence: 90%
“…Regarding N concentration, several studies have found that PGPR can increase the N levels in tomato and zucchini shoots [10,63,64]. However, in the present study, PGPR application did not increase the N levels in plant shoots in both experiments.…”
Section: Discussioncontrasting
confidence: 90%
“…A high level of Ca was found to exist in the humus layer of contaminated soils where root ramification was impaired [64]. When soil environment was improved to benefit foraging by ramifying root crossings, Ca uptake did not accord [65]. Instead, root foraging sensitivity was lowered by the high Ca level in P. asiatica, which was driven by fine root tip number.…”
Section: Root Foraging Behavior and Driving Forces From Fine Root Mor...mentioning
confidence: 99%
“…Nitrogen is not only an essential nutrient element for plant growth and development but also a limiting element for plant growth [38,39]. Nitrogen in soil mainly exists in two forms: organic nitrogen and inorganic nitrogen.…”
Section: Response Of Nitrogen Transformation In Paddy Soil To Azolla ...mentioning
confidence: 99%